1994
DOI: 10.2503/jjshs.63.515
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Lateral and Primary Leaves to the Development and Quality of 'Kyoho' Grape Berry

Abstract: SummaryThe contribution of lateral and primary leaves to the growth and quality of 'Kyoho' (Vitis vinifera × V. labrusca) berries was investigated. The total leaf area on each bearing shoot was adjusted to ca. 1500 cm2 by removing primary or lateral leaves at veraison so that the percentage of lateral leaf area (LL) beyond or distal to the cluster was : ca. 100 (100 -LL), 70 (70 -LL), 30 (30 -LL), and 0 (0 -LL) of the ca. 1000 cm2.The net photosynthetic rate (Pn) of the primary and lateral leaves on treated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…According to Poni and Intrieri (1996) topping should be calibrated to promote lateral shoots which become mature around veraison. Younger leaves on these laterals are more active photosynthetically than older main leaves and enhance fruit quality by exporting assimilates to the ripening grapes (Hirano et al 1994, Koblet et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…According to Poni and Intrieri (1996) topping should be calibrated to promote lateral shoots which become mature around veraison. Younger leaves on these laterals are more active photosynthetically than older main leaves and enhance fruit quality by exporting assimilates to the ripening grapes (Hirano et al 1994, Koblet et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Partial defoliation of shoots enables exposure of berries to enrich them with photosyntethates thanks to the enhanced photosynthetic activity of the remainder of leaves (Hunter, Visser 1988), which corresponds with the best results obtained on treatments III and IV, where the lateral shoots were not removed, but just hedged at leaf 2. Hirano et al (1994) proved that lateral foliage fastens the photosynthetic rate compared with primary foliage, which results in increased accumulation of sugar. In addition, Vasconcelos and Castagnoli (2000) confirmed that lateral shoots accelerate fruit ripening and suggest that this technique can improve fruit composition in short-season regions.…”
Section: Sugar Concentration Of Harvested Grapesmentioning
confidence: 99%